Empty Nose Syndrome May Be the Chief Criminal Behind Many of the Worst Atrocities against Rhinologic Medical Staff in China - Feng-Biao Wen; Song Zhao; Yang Yang; Dong-Lei Liu; Kai Wu (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
On Sep 3, 2012, several rhinology specialized medical staff members in Shenzhen Pengcheng Hospital were stabbed by a patient with blood-covered hands; on Oct 25, 2013, a chief physician of the otolaryngology department of the first People's Hospital of Wenling, was killed in his clinic while working on a patient. The recent events of violence against doctors in China have caused great shock throughout most of the country. We can't help wanting to ask: Who is at the bottom of all these troubles? Speaking of this problem, Empty nose syndrome (ENS) is an unavoidable topic. In the past decade, ENS is becoming increasingly common iatrogenic disorder but poorly understood resulting from the destruction of normal nasal tissue [1]. ENS may have murdered many rhinologic medical staff indirectly, whereas this disease is still "fresh" in China because of lacking of enough attention and research about ENS in the general Chinese Medical Community.